Vacuolar protein sorting-associated protein 72 homolog (VPS72) binding to lysine acetyltransferase 5 (KAT5) promotes the proliferation, invasion and migration of hepatocellular carcinoma through regulating phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway. Issue 4 (1st April 2022) - Chen, Tiejun; Tu, Yinuo; Lv, Dongnuo; Lin, Kunpeng; Tang, Hui; Huang, Wenjie
ABSTRACT: Hepatocellular carcinoma, a fatal malignancy that occurs in the liver, poses a major public health challenge. This paper attempted to clarify the role and mechanism of vacuolar protein sorting-associated protein 72 homolog (VPS72) in the progression of hepatocellular carcinoma. Firstly, VPS72 expression in hepatocellular carcinoma tissues and the prognostic correlation were analyzed by GEPIA2 database. Western blotting and RT-qPCR assays were used to evaluate VPS72 expression in several hepatocellular carcinoma cell lines. Then, cell proliferation was assessed by cell counting kit-8 and colony formation in HuH-7 cells with VPS72 silencing. Measurement of cell invasion and migration by transwell and wound healing assays. Next, the relationship between VPS72 and lysine acetyltransferase 5 (KAT5) was predicted by bioGRID, STRING and GEIPA2 databases, which was confirmed by Co-immunoprecipitation assay. Subsequently, KAT5 was overexpressed to explore whether VPS72 could regulate the progression of hepatocellular carcinoma by binding to KAT5. And the expression of proteins related to PI3K/AKT signaling was tested with western blotting. Results indicated that VPS72 was highly expressed in hepatocellular carcinoma tissues and cell lines and was associated with poor prognosis. VPS72 knockdown inhibited the proliferation, invasion and migration of HuH-7 cells. In addition, VPS72 could bind to KAT5. KAT5 overexpression reversed the suppressive impacts of VPS72 knockdown on the proliferation, invasion and migration in HuH-7 cells. Besides, VPS72 silencing downregulated p-PI3K and p-AKT expression, which was restored by KAT5 overexpression. Collectively, VPS72 binding to KAT5 promotes the progression of hepatocellular carcinoma through the regulation of PI3K/AKT signaling pathway. Graphical Abstract: uf0001